Immobilization of Cofactor Self-Sufficient Recombinant Escherichia coli for Enantioselective Biosynthesis of (R)-1-Phenyl-1,2-Ethanediol - Peng, Fei; Su, Hui-Hui; Ou, Xiao-Yang; Ni, Zi-Fu; Zong, Min-Hua; Lou, Wen-Yong (Frontiers in Bioengineering and Biotechnology, 2020)
(R)-1-phenyl-1,2-ethanediol is an important synthon for the preparation of β-adrenergic blocking agents. This study identified a (2R,3R)-butanediol dehydrogenase (KgBDH) from Kurthia gibsonii SC0312, which showed high enantioselectivity for production of (R)-1-phenyl-1,2-ethanediol by reduction of 2-hydroxyacetophenone. KgBDH was expressed in a recombinant engineered strain, purified and characterized. It showed good catalytic activity at pH 6-8 and better stability in an alkaline (pH 7.5-8) than an acidic environment (pH 6.0-7.0), providing approximately 73% and 88% of residual activity after 96 h at pH 7.5 and 8.0, respectively. The maximum catalytic activity was obtained at 45 °C; nevertheless, poor thermal stability was observed at >30 °C. Additionally, the examined metal ions did not activate the catalytic activity of KgBDH. A recombinant Escherichia coli strain co-expressing KgBDH and glucose dehydrogenase was constructed and immobilized via entrapment with a mixture of activated carbon and calcium alginate via entrapment. The immobilized cells had 1.8-fold higher catalytic activity than that of cells immobilized by calcium alginate alone. The maximum catalytic activity of the immobilized cells was achieved at pH 7.5, and favorable pH stability was observed at pH 6.0-9.0. Moreover, the immobilized cells showed favorable thermal stability at 25-30 °C and better operational stability than free cells, retaining approximately 55% of the initial catalytic activity after four cycles. Finally, 81% yields (195 mM product) and > 99% ee of (R)-1-phenyl-1,2-ethanediol were produced within 12 h through a fed-batch strategy with the immobilized cells (25 mg/mL wet cells) at 35 °C and 180 rpm, with a productivity of approximately 54 g/L per day.